Cognition and emotion : reviews of current research and theories - Houwer, Jan de.; Hermans, Dirk. (Hove, East Sussex ; New York, NY : Psychology Press, 2010)
"Clearly written by international experts, this excellent book provides authoritative overviews of the most interesting and challenging debates in cognition and emotion. Both established researchers and students new to the field will warmly welcome such clear statements of what questions have already been asked, what controversies remain, and what the future of the field may hold." Mark Williams, Wellcome Principal Research Fellow & Professor of Clinical Psychology, University of Oxford, UK --
"This is an important book. It offers a collection of cutting-edge reviews of research on a number of basic processes in emotions, such as preattentive processes and valence assessment. It demonstrates that the experimental study of emotion processes has entered a new stage in probing basic pshychological mechanisms." Nico H. Frijda, Emeritus Professor of Psychology, University of Amsterdam, The Netherlands --
"The overall quality of these reviews is exceptionally high-each has been refined using rigorous peer review and editorial expertise. The resulting chapters are balanced and comprehensive, yet present distinctive points of view. This stimulating book represents the state of the art in understanding the relation between emotion and cognition." W. Gerrod Parrott, Professor of Psychology, Georgetown University, USA --
Emotions are complex and multifaceted phenomena. Although they have been examined from a variety of perspectives, the study of the interaction between cognition and emotion has always occupied a unique position within emotion research. --
During the past 30 years, research on the relationship between cognition and emotion has boomed and so many studies on this topic have been published that it is difficult to keep track of the evidence. This book fulfils the need for a review of the existing evidence on particular aspects of the interplay between cognition and emotion. --
This collection of state-of-the-art reviews of the most important topics in cognition and emotion research covers: emotion theories, feeling and thinking, the perception of emotion, the expression of emotion, emotion regulation, emotion and memory, and emotion and attention, By bringing these reviews together, this book presents a unique overview of the knowledge that has been generated in the past decades about the many and complex ways in which cognition and emotion interact. --Book Jacket.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Emotions and cognition; Emotions; Cognition; Electronic books